Determination of Chemical Composition and Antimicrobial Activity of the CO2 Extract of Eryngium planum L. - Arykbayeva, Aliya B.; Ustenova, Gulbaram O.; Sharipov, Kamalidin O.; Beissebayeva, Ulzhan T.; Kaukhova, Irina E.; Myrzabayeva, Auyes; Gemejiyeva, Nadezhda G. (International Journal of Biomaterials, 2023)
The article presents parameters for obtaining a carbon dioxide extract from the subterranean part of Eryngium planum that contains a valuable set of organic substances and has a certain antimicrobial effect. Methods. Raw materials were collected in the Almaty region (Republic of Kazakhstan). The CO2 extract of Eryngium planum herbs was obtained under subcritical conditions. A gas chromatograph with a mass spectrometric detector was used to determine the compositional breakdown of the extract. Antimicrobial activity was determined by two methods: the micromethod of serial dilutions and the disk-diffusion method. Three microbial test strains were used: Staphylococcus aureus ATCC 6538-P, Escherichia coli ATCC 8739, and Candida albicans ATCC 10231. Results. To extract biologically active substances from the subterranean part of Eryngium planum L., we have chosen carbon dioxide extraction technology, a technology for processing carbon dioxide (CO2) raw materials, which allows us to extract various substances in high concentrations. Carbon dioxide extraction technology is an effective and environmentally safe way to isolate various biologically active substances contained in medicinal plant raw materials. In the composition of the CO2 extract of Eryngium planum L. 43 components were identified, the main of which are α-linolenic acid, 8.30%; myristic acid, 6.40%; caryophyllene, 6.92%; spatulous, 6.62%; and other main identified compounds and their percentage. Conclusions. The study showed that the CO2 extract of Eryngium planum L. contains biologically active compounds that have a pronounced antimicrobial effect against clinically significant microorganisms, such as Escherichia coli, Staphylococcus aureus, and Candida albicans.